KELIMPAHAN HAMA KUTU PADATANAMAN JERUK SIAM (Citrus nobilis Lour.) DI DESA KUOK KECAMATAN KUOK KABUPATEN KAMPAR PROVINSI RIAU - Dessy Dian Syafitri; Hafiz Fauzana; Desita Salbiah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The fundamental principles of integrated pest management system is monitoring ecosystem. An important aspect in monitoring ecosystem is observation the abundance of aphids and mealybugs the Citrus nobilis. The purpose of this research is to determine the abundance of aphids and mealybugs the Citrus nobilis Lour. in the of Village Kuok Kuok District Kampar Regency Riau Province. The research using survey method. Observation location was determined by selecting two gardens. Plant samples was determined to the method of systematic sampling with a zig zag pattern. Method was doing of aphids and mealybugs in two types by direct taking on plants and with Moericketraps. Parameters observation were description locations, species identification and total individual ofaphids and mealybugs, abundance of aphids and mealybugs and the persentage attack of aphids and mealybugs. The result showed that abundance of aphids and mealybugs in Citrus nobilis were Toxoptera sp., Aphis gossypii, Aonidiella aurantii, Lepidosaphes beckii, Myzus persicae, aleurocanthus woglumi, Bemisia tabaci and Planococcus citri species. The highest abundance of aphids and mealybugs species in Citrus nobilis was Toxoptera sp. with 98.90 individual per plant and relative abundance of 37.15%. Keywords: Citrus nobilis Lour., Aphids and Mealybugs, Abundance